2022
DOI: 10.31332/lkw.v0i0.3927
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Citizenship Values in Arabic Textbooks: Marrying Delanty and Hopkins Concepts

Abstract: Although research on citizenship values in language textbooks has been widely documented, little is known about citizenship values in Arabic textbooks at Indonesian Islamic Junior High Schools. To extend this scholarship, the present study examines the values of citizenship in those textbooks and how they are presented. Data collection was carried out using document analysis techniques in three textbooks. Data analysis was carried out using a combination of Delanty and Hopkins concepts of citizenship values. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…On the other hand, the analysis of the values in textbooks also sparked the researchers' interest. Studies by Al-fanani & Yusuf (2021), Kuraedah (2022), and Naufal (2022) found that the Arabic textbook published by the Indonesian Ministry of Religious Affairs needs to contain adequate Indonesian values. Textbooks are dominated by Arabic and Middle Eastern values, which are inappropriate for students' learning contexts (Al-fanani & Yusuf, 2021;Kuraedah, 2022;Naufal, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the analysis of the values in textbooks also sparked the researchers' interest. Studies by Al-fanani & Yusuf (2021), Kuraedah (2022), and Naufal (2022) found that the Arabic textbook published by the Indonesian Ministry of Religious Affairs needs to contain adequate Indonesian values. Textbooks are dominated by Arabic and Middle Eastern values, which are inappropriate for students' learning contexts (Al-fanani & Yusuf, 2021;Kuraedah, 2022;Naufal, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Al-fanani & Yusuf (2021), Kuraedah (2022), and Naufal (2022) found that the Arabic textbook published by the Indonesian Ministry of Religious Affairs needs to contain adequate Indonesian values. Textbooks are dominated by Arabic and Middle Eastern values, which are inappropriate for students' learning contexts (Al-fanani & Yusuf, 2021;Kuraedah, 2022;Naufal, 2022). The domination of Arab cultural values in the textbook does not follow the orientation of multicultural education (Kuraedah et al, 2022;Naufal, 2022).…”
Section: Introductionmentioning
confidence: 99%